Analisis Pemasaran Bawang Merah (Allium Ascalonicum L) di Kebun Praktek Fakultas Teknologi Pangan Pertanian dan Perikanan Universitas Nusa Nipa Kelurahan Kota Uneng Kecamatan Alok Kabupaten Sikka - Gore, Sisislia Aurelia; Noni, Sarlina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Marketing Performance is a parameter to assess the success or failure of a business, because the ultimate goal of the production process is sales in the hope of getting a profit. Shallot marketing is an activity of delivering shallot commodities from farmers to consumers with the aim of getting value for money in return for the results of the commodity. The purpose of this study is to determine the analysis of shallot marketing in the practice garden of the Faculty of Food Technology, Agriculture and Fisheries, Nusa Nipa University. The analysis method used in this study is descriptive, which is a method that knows and provides an overview of primary data and secondary data that have been collected. The results showed that: 1). Shallot marketing in the practice garden of the faculty of agricultural food technology and fisheries there are three marketing channels, namely: in Marketing channel I, producers sell their shallots to consumers, in marketing channel II, producers sell their shallots to retailers then from retailers sold to consumers and Marketing channel III, farmers sell to collecting traders then from collecting traders resell them to wholesalers Then wholesalers sell to retailers, after which they are marketed to consumers. 2). If you see that the most efficient onion marketing channel is in marketing channel II by 6.76%. Keywords: consumer satisfaction, cost efficiency.